Utilizing and managing commerce and services online - Khosrowpour, Mehdi, 1951- (Hershey, PA : Cybertech Publishing, 2007)
"This book provides comprehensive coverage and understanding of the social, cultural, organizational, and cognitive impacts of e-commerce technologies and advances in organizations around the world. E-commerce strategic management, leadership, organizational behavior, development, and employee ethical issues are only a few of the challenges presented in this all-inclusive work"--Provided by publisher.
Managing online customer service operations / David Barnes -- Firm value effects of web site redesign / Raquel Benbunan-Fich, Eliezer M. Fich -- Jurisdiction in B2C e-commerce dispute within European Union / Ong Ching Eang -- Failures of B2C retailing : a services industry view / Anil M. Pandya, Nikhilesh Dholakia -- Inducing online trust in e-commerce : empirical investigations on web design factors / Ye Diana Wang, Henry H. Emurian -- Public perception : a newspaper medium perspective : e-commerce in Australian manufacturing (revisited) / Jing Gao -- Netrepreneur simulation : the development of realism in virtual e-entrepreneurship learning / Salim Jiwa, Dawn Lavelle, Arjun Rose.
Includes bibliographical references and index.
Keywords: Electronic commerce -- Management; Electronic commerce -- Technological innovations; Electronic commerce -- Computer network resources; Internet